Attack height and jump height for men`s volleyball players - Hsieh, C. T.; Lamm, Z. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this current study was to investigate the factors that associate with the ball contact height for men`s volleyball players and the difference between good and poor volleyball players. Ten male collegiate volleyball players (club teams) were recruited (BH: 1.82 ± 0.09m; BW: 80.13 ± 13.22kg). Each subject performed 3 successful trials of volleyball attack performance by hitting the ball above the net and inside the boundary. 3D motion analysis (3 digital cameras) was used to obtain kinematic data of the performance. Results indicated that ball contact height was significantly associated with takeoff and reach height. When all heights were normalized to body height, player`s body positions at instant of takeoff and ball contact are important to ball contact height.